2013
DOI: 10.1111/cgf.12090
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Visual Exploration: Evaluation With Expert Users

Abstract: We present an Evolutionary Visual Exploration (EVE) system that combines visual analytics with stochastic optimisation to aid the exploration of multidimensional datasets characterised by a large number of possible views or projections. Starting from dimensions whose values are automatically calculated by a PCA, an interactive evolutionary algorithm progressively builds (or evolves) non-trivial viewpoints in the form of linear and non-linear dimension combinations, to help users discover new interesting views … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…For correlation questions, EvoGraphDice uses an interactive scatterplot matrix generated by evolutionary algorithm to help users discover complex relationships in multi-dimensional data [4]. For research questions involving differences, we discuss the existing tools below.…”
Section: Software Support In Empirical Researchmentioning
confidence: 99%
“…For correlation questions, EvoGraphDice uses an interactive scatterplot matrix generated by evolutionary algorithm to help users discover complex relationships in multi-dimensional data [4]. For research questions involving differences, we discuss the existing tools below.…”
Section: Software Support In Empirical Researchmentioning
confidence: 99%
“…ForceSPIRE [24] is an example of such interactions (e.g., moving, annotating and highlighting) that re-weight the term dimensions in the distance metric and recalculate similarities among documents. EvoGraphDice [11,14] employed a similar idea to dynamically change a scatterplot matrix. Object-LI enable users to focus on the data and perform exploratory analysis (for Bicluster-LR and Chain-LR ) by implicitly tuning the algorithm parameters.…”
Section: Four-level Of Interaction Designmentioning
confidence: 99%
“…Recent extensions, described in [3], are (i) a Genetic Programming (GP) algorithm allowing the manipulation of nonlinear combinations of dimensions as variable size mathematical formulae, (ii) user assessment of proposed views is explicitly captured via a slider, (iii) a surrogate function based on some specific geometric measurements (scagnos- Figure 2: Nine scagnostics measures from [16].…”
Section: Evographdice Visual Interfacementioning
confidence: 99%
“…In [3], we validated our general approach of combining visual analytics with stochastic optimisation to aid data exploration, by conducting an observational study with expert users from various domains. Our results showed that EvoGraphDice can help users quantify qualitative hypotheses and try out different scenarios to dynamically transform their data.…”
Section: Evographdice Visual Interfacementioning
confidence: 99%
See 1 more Smart Citation